The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ddr.21322
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Metformin against Acute Inflammation and Oxidative Stress in Rat

Abstract: Preclinical Research The antidiabetic drug, metformin, can inhibit the release of inflammatory mediators in several disease conditions. The present study was carried out to evaluate the efficacy of metformin in ameliorating edema formation, oxidative stress, mediator release and vascular changes associated with acute inflammation in the rat carrageenan model. Metformin dose-dependently inhibited paw swelling induced by carrageenan and normalized the tissue levels of the inflammatory markers myeloperoxidase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 42 publications
(45 reference statements)
3
14
0
Order By: Relevance
“…In addition to reducing blood glucose, it also has a kidney protection effect, which can reduce the urinary albumin excretion rate in DN patients . Metformin also has antioxidant and inhibitory effects on inflammation . The exact protective mechanism of metformin on DN is unknown, and research suggests that it may be related to the following signaling pathways, including the TGF-β1/Smad2/3 pathway, AMPK/mTOR pathway, epithelial–mesenchymal transition (EMT), oxidative stress, and inflammation, which were consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to reducing blood glucose, it also has a kidney protection effect, which can reduce the urinary albumin excretion rate in DN patients . Metformin also has antioxidant and inhibitory effects on inflammation . The exact protective mechanism of metformin on DN is unknown, and research suggests that it may be related to the following signaling pathways, including the TGF-β1/Smad2/3 pathway, AMPK/mTOR pathway, epithelial–mesenchymal transition (EMT), oxidative stress, and inflammation, which were consistent with our findings.…”
Section: Discussionsupporting
confidence: 90%
“… 12 , 19 It has been reported to protect against doxorubicin-induced hepatic toxicity. 10 Its hepatoprotective activity occurs via antioxidant, anti-inflammatory, and anti-apoptotic mecha- nisms 10 , 20 , 21 ; as well as via activation of adenosine 50-mono- phosphate-activated protein kinase. 12 …”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that MTF inhibits mitochondrial respiratory chain complex I and generates low levels of oxidants, which induce the antioxidant response producing a hormetic effect. At the same time, reduced ATP levels activate AMPK, which activates diverse protective pathways [17]. It has been proposed that MTF prevents the damage caused by sedentary lifestyle by increasing the capacity of muscular performance [18], so MTF has been proposed as a geroprotective drug that can decrease the rate of aging [19, 20].…”
Section: Introductionmentioning
confidence: 99%